Visualizing acyl carrier protein interactions within a crosslinked type I polyketide synthase - Jiang, Ziran; Heberlig, Graham W.; Chen, Jeffrey A.; Huynh, Jennifer; La Clair, James J.; Burkart, Michael D. (Nature communications, 2025)
Using a combination of dual covalent crosslinking and cryo-EM analyses, we elucidate the structure of mycocerosic acid synthase from Mycobacterium tuberculosis trapped in two distinct catalytic states during its iterative cycle. These structures reveal domain architecture of the acyl carrier protein mediating condensation and dehydration through dual site-selective crosslinking of the acyl carrier protein with the ketosynthase and dehydratase domains. Map density was sufficient to visualize full domain architecture with active site-bound probes and elucidate key interactions of four distinct crosslinked species. Here, iterative vectorial polyketide biosynthesis arises through an overall twisting and tilting architecture, enabling positioning and entry of the cognate substrate at each enzymatic domain. These structures present valuable details for future therapeutic design against mycocerosic acid biosynthesis in M. tuberculosis . Bacterial Type I polyketide synthases are responsible for producing both lifesaving medicines and virulence factors, yet their stepwise mechanism remains elusive. Here, Burkart et al. characterize acyl carrier protein bound states of mycocerosic acid synthase from Mycobacterium tuberculosis through crosslinking and cryo-EM.